Peran Undang-Undang Dasar 1945 dalam Menjamin Hak Asasi Manusia di Indonesia - Andika Dwi Maizal; Edy Soestanto (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
The 1945 Constitution (UUD 1945) has a very iportant fundamental role in the legal and political system in Indonesia, especially in ensuring the fulfillment of Human Rights (HAM) for the people in Indonesia. As the country's highest constitution, the 1945 Constitution not only determines the structure and powers of the state, but also regulates the protection of the rights of individuals and groups of citizens or society. Since the amendments to the 1945 Constitution from 1999 to 2002, the substance of human rights has increasingly been strengthened and regulations have been tightened, with an emphasis on civil, political, economic, social and cultural rights. In this article I aim to examine how the 1945 Constitution functions as a legal instrument to guarantee the protection of human rights in Indonesia. This research uses a normative approach by analyzing articles in the 1945 Constitution which are directly or indirectly related to human rights, as well as assessing their implementation in practice. The results of the analysis show that although the 1945 Constitution provides a strong legal foundation for the protection of human rights, many challenges still arise in its implementation and enforcement, especially those related to the gap between legal norms and the reality on the ground. Apart from that, the role of state institutions such as the Constitutional Court (MK), Komnas HAM, and the judicial system is very crucial in ensuring the fulfillment of citizens' basic rights. In conclusion, the 1945 Constitution has great potential to guarantee Human Rights in Indonesia, but ongoing efforts are needed to overcome various obstacles and problems in its implementation practice.